ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN KAMAR PADA HOTEL CITRA III KOTA METRO - Ulan Oktariana; Suyanto Suyanto; Sri Retnaning Rahayu (Jurnal Akuntansi AKTIVA, 2023)
This study aims to determine the accounting information system for room sales, cash receipts and disbursements at Hotel Citra III Metro City. Data obtained from observations, documentation and interview results. Research data analysis was carried out using qualitative descriptive data analysis. The results showed that the room sales accounting information system at Citra III Hotel Metro City was not yet effective, because there were still weaknesses in its internal control, namely supervision of the accounting information system, especially in the room sales accounting information system.